2020
DOI: 10.3390/ijerph17165649
|View full text |Cite
|
Sign up to set email alerts
|

Health and Wellness Status Perception of Half-Marathon Runners: Influence of Age, Sex, Injury, and Training with Qualified Staff

Abstract: The aim of this study was to analyze the health and wellness status perception in amateur half-marathon runners according to sex, age, being injured or not during the two months prior to the race, and having the support or not of qualified staff for race preparation. Six hundred and twenty-four amateur level half-marathon athletes (515 men and 107 women; 41.5 ± 10.1 years) participated in the study. One week before competing in a half-marathon, participants answered the Hooper Index and the SF-36 questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…However, runners of shorter distances (i.e., half-marathon) may also profit from professional advice. A current study investigating recreational half-marathoners showed that athletes supported by a qualified staff for race preparation showed better results in the dimensions of physical function and emotional role ( Romaratezabala et al, 2020 ).…”
Section: Discussionmentioning
confidence: 97%
“…However, runners of shorter distances (i.e., half-marathon) may also profit from professional advice. A current study investigating recreational half-marathoners showed that athletes supported by a qualified staff for race preparation showed better results in the dimensions of physical function and emotional role ( Romaratezabala et al, 2020 ).…”
Section: Discussionmentioning
confidence: 97%
“…Endurance runners may use different approaches to prepare themselves for running events [ 15 ]. Research suggests that being under the supervision of experts and professionals could bring about beneficial health- and performance-related advantages for endurance runners [ 39 , 40 ]. Data from the present study show that 9 in 10 runners train and prepare themselves for running competitions independently without supervision mostly (about 3 in 4) within less than four months.…”
Section: Discussionmentioning
confidence: 99%
“…However, race distance could greatly affect training volume, as it has been shown that half-marathoners focus more on training speed, while ultra-marathoners concentrate more on training duration [ 38 ]. In this regard, supervision from a specialist could result in beneficial advantages in training adaptations and running performance [ 39 , 40 ]. When comparing race distances, evidence shows that endurance runners competing in long distances (i.e., marathon and ultra-marathon) have a greater tendency to be supervised by a specialist (e.g., sports scientists, sport medicine physicians) [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Training under the supervision of a specialist could result in beneficial advantages for the health and performance of endurance runners [40,41]. Recent evidence has shown that endurance runners participating in longer distances (i.e., marathon and ultra-marathon) benefit from receiving more professional support in different phases of training and racing compared to runners competing in shorter distances (i.e., 10 km, half-marathon) [8].…”
Section: Discussionmentioning
confidence: 99%